If you find a rock - Christian, Peggy; Lember, Barbara Hirsch (San Diego, CA : Harcourt, Brace & Co., 2000)
Celebrates the variety of rocks that can be found, including skipping rocks, chalk rocks, and splashing rocks.
Adult 930
Accelerated Reader AR
Keywords: Rocks -- Juvenile literature; Rocks